Genetic Relatedness among Helicobacter pullorum Isolates from Broiler Chickens - Wai , Soe Soe; Saleha, A.A.; Zunita, Z.; Hassan, L.; Jalila, A.; Shah, A.H. (International Journal of Poultry Science, 2014)
Helicobacter pullorum, an enterohepatic helicobacter with the ability to colonize the intestine and liver of avian species, mice and humans, is increasingly recognized as a food borne zoonotic pathogen. The present study aimed to determine the genetic similarity among H. pullorum using pulsed field gel electrophoresis (PFGE) with SacII and SmaI restriction endonucleases (REs) digestion. The H. pullorum were isolated from broiler chickens in eight farms. Within-farm genetic profiling of isolates showed close relationship (>95%); however genetic diversity was observed between isolates from different farms. Digestion of genome with SacII yielded two clusters comprised 16 pulsotypes, 8-14 DNA bands with a molecular weight ranging from 40 to 400 kb whereas SmaI digested genome produced two clusters with 14 pulsotypes, 7 to 13 DNA bands with molecular weight ranging from 40 to 250 kb. The RE SacII showed a higher discriminatory power compared to SmaI. In conclusion, within-farm genetic similarity of isolates suggested the same source of clonal origin.